Rubbish increases yields - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
Farmers near Thies, Senegal have been loading up their donkey carts with untreated household rubbish from the town tip and spreading it on their land. This cheap source of fertilizer led to better crop yields and other farmers, seeing the benefits,...